2000
DOI: 10.1152/jn.2000.83.4.2047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lesions of the Oculomotor Cerebellar Vermis on Eye Movements in Primate: Smooth Pursuit

Abstract: We studied the effects on smooth pursuit eye movements of ablation of the dorsal cerebellar vermis (lesions centered on lobules VI and VII) in three monkeys in which the cerebellar nuclei were spared. Following the lesion the latencies to pursuit initiation were unchanged. Monkeys showed a small decrease (up to 15%) in gain during triangular-wave tracking. More striking were changes in the dynamic properties of pursuit as determined in the open-loop period (the 1st 100 ms) of smooth tracking. Changes included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
106
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(115 citation statements)
references
References 39 publications
8
106
1
Order By: Relevance
“…Simple spikes in the flocculusparaflocculus complex are modulated by smooth pursuit or ocular following eye movements (Lisberger and Fuchs 1978;Miles et al 1981;Nagao 1992;Noda and Mikami 1986;Shidara and Kawano 1993;Stone and Lisberger 1990). Bilateral lesions of vermal lobules VI/VIIA induced saccade hypometria, slightly delayed saccade onsets (Takagi et al 1998;Barash et al 1999), and decreased smooth pursuit velocity (Takagi et al 2000). Simple spike activity in the vermal lobulus VI/VIIA are modulated by saccade (Catz et al 2005;Kase et al 1980;Ohtsuka and Noda 1995;Sato and Noda 1992;Thier et al 2000) and smooth pursuit eye movements (Suzuki and Keller 1988a,b;Suzuki et al 1981).…”
Section: Voluntary Eye Movement Control By Oculomotor Cerebellummentioning
confidence: 99%
See 1 more Smart Citation
“…Simple spikes in the flocculusparaflocculus complex are modulated by smooth pursuit or ocular following eye movements (Lisberger and Fuchs 1978;Miles et al 1981;Nagao 1992;Noda and Mikami 1986;Shidara and Kawano 1993;Stone and Lisberger 1990). Bilateral lesions of vermal lobules VI/VIIA induced saccade hypometria, slightly delayed saccade onsets (Takagi et al 1998;Barash et al 1999), and decreased smooth pursuit velocity (Takagi et al 2000). Simple spike activity in the vermal lobulus VI/VIIA are modulated by saccade (Catz et al 2005;Kase et al 1980;Ohtsuka and Noda 1995;Sato and Noda 1992;Thier et al 2000) and smooth pursuit eye movements (Suzuki and Keller 1988a,b;Suzuki et al 1981).…”
Section: Voluntary Eye Movement Control By Oculomotor Cerebellummentioning
confidence: 99%
“…Ablation, chemical inactivation, and electrical stimulation studies in monkeys suggest that the parietal middle temporal (MT) and medial superior temporal (MST) areas (e.g., Newsome et al 1985) and the frontal eye field (FEF) (Bruce and Goldberg 1985;Bruce et al 1985;Keating 1991;Keating et al 1996;Lynch 1987;Shi et al 1998) are the important cerebral areas for smooth pursuit and saccades. Lesion studies in monkeys suggest that the flocculus-paraflocculus complex (Hiramatsu et al 2008;Rambold et al 2002;Zee et al 1981) and vermal lobule VI/VIIA (Barash et al 1999;Takagi et al 1998Takagi et al , 2000 are the relevant cerebellar areas. Moreover, lesions in the vermal lobule VI/VIIA impaired the adaptation of saccade amplitude induced by double step paradigms (Barash et al 1999;Takagi et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Gutierrez-Garralda et al (2013) showed that basal ganglia patients exhibit normal learning in a dart throwing task when the visual scene is horizontally displaced but impaired performance when the visual scene is mirror reversed (but see Stebbins et al, 1997;Laforce and Doyon, 2001). The basal ganglia have been associated with action selection (Gerardin et al, 2004) and the acquisition of new control policies (Doya, 2000;Middleton and Strick, 2000;Hikosaka et al, 2002;Boyd et al, 2009; In contrast, the adaptation of eye movements (Takagi et al, 1998(Takagi et al, , 2000, arm movements (Martin et al, 1996;Tseng et al, 2007), and gait (Reisman et al, 2007) heavily depends on the integrity of the cerebellum, whereas basal ganglia-associated disorders affect adaptation to a lesser degree (Fernandez-Ruiz et al, 2003;Marinelli et al, 2009;Gutierrez-Garralda et al, 2013).…”
mentioning
confidence: 99%
“…1 Neural processing of SP involves the frontal, 2 temporal, and parietal lobes, 3 the brainstem tegmentum, and the cerebellum. [4][5][6] Chiari type II malformation (CII) is a congenital deformity of the brainstem and cerebellum that is associated with myelomeningocele. In CII, the posterior fossa is small and, as a result, its contents are distorted as they herniate through the tentorial incisura and the foramen magnum.…”
mentioning
confidence: 99%